Clinical translation of human iPSC technologies: advances, safety concerns, and future directions - Dhaiban, Sarah; Chandran, Sanjana; Noshi, Mohammed; Sajini, Abdulrahim A. (Frontiers in Cell and Developmental Biology, 2025)
Human induced pluripotent stem cells (hiPSCs) have opened new possibilities in regenerative medicine, providing a versatile platform for modeling human disorders, testing pharmacological agents, and developing personalized regenerative treatments. By reprogramming adult cells into a pluripotent state, scientists can generate patient-specific cells capable of differentiating into nearly any tissue type. Using the patient’s own cells allows for therapies that are both biologically matched and ethically acceptable, while also reducing the likelihood that the immune system will reject transplanted cells. Despite this promise, translating hiPSCs into routine clinical use has proven challenging, with several practical and biological barriers yet to be overcome. Key concerns include variability in differentiation outcomes, immune responses to allogeneic cells, genetic and epigenetic abnormalities, and the risk of tumor formation. Reliable scale-up under GMP conditions remains a major technical hurdle, and critical questions around long-term engraftment, tissue integration, and immune tolerance are still unresolved. Recent advances, including CRISPR/Cas9 gene editing and AI-guided differentiation, are enhancing iPSC quality and enabling treatments to be tailored to individual patients. Clinical trials are ongoing in areas such as retinal disorders, neurodegenerative diseases, cardiac conditions, and cancer immunotherapy, with early findings suggesting these therapies may be both feasible and safe. However, widespread adoption will require rigorous, long-term evaluation. This review examines the latest progress in hiPSC technology and evaluates its movement toward clinical translation. We highlight the major challenges that continue to limit broader application, particularly those related to safety, large-scale manufacturing, and regulatory oversight, and discuss emerging advances that may help bring iPSC-based therapies closer to routine clinical practice.